Improving Nutritional and Functional Quality by Genome Editing of Crops: Status and Perspectives - Ku, Hyung-Keun; Ha, Sun-Hwa (Frontiers in Plant Science, 2020)
Genome-editing tools including meganucleases, zinc finger nucleases, transcription activator-like effector nucleases and clustered regularly interspaced short palindromic repeats (CRISPR) system have been applied to improve the quality of staple, oilseed, and horticultural crops with great accuracy and efficiency compared to conventional breeding. In particular, the CRISPR method has proven to be the most feasible, cost-effective and versatile tool allowing precise and efficient editing of plant genomes in recent years, showing great potential in crop improvement. Until now, various genome-edited crops with enhanced commercial value have been developed by not only at global companies but also small laboratories in universities, suggesting low barriers in manpower and capital to entry. In this study, we review the current applications of genome editing technologies to improve the nutritional and functional quality and the preferred traits of various crops. Combining this rapidly advancing genome-editing technology and conventional breeding will greatly extend the potential of genome-edited crops and their commercialization.